Obtaining the fine-grained silicon carbide, used in the synthesis of construction ceramics; Resource-Efficient Technologies; Vol. 2, Iss. 2 - Karelin V. A. Vladimir Aleksandrovich; Strashko A. N. Aleksander Nikolaevich; Sazonov A. V.; Dubrovin A. V. (2016, 2016)
Title screen